KIAT SUKSES MENGEMBANGKAN WIRAUSAHA - Siti Salbiyah (UMSurabaya Publishing, 2008)
Abstract ”Help each other in doing good and pious, and do not help one another in sin and transgression” (Letter (5) Al - Maidah 2). The best manis for the benefit of other humans. The phrase provides learning for all human beings as social beings who have been equipped with the properties of solidarity by God the Creator of the social skills are encouraged to reflect on it in the form of deeds/actions that could provide benefits for himself or others. Deeds and actions that could provide benefits for himself and others that must be oriented to the future as a deed which contains the value of worship, so it needs to start with the intention of seeking ridholillah and done with full sincerity in order to be grateful for every blessing that has been given to us as humans, such as health, ability to work hard, be creative and innovation, and others. For individuals who do the deeds / actions coupled with the intention of seeking ridholillah and being grateful, of course, will appear personal traits that promote honesty, discipline, responsibility, and are oriented towards the interests of the market or customers. Therefore we so successful entrepreneurship, the necessary, discipline, responsibility, and are Oriented towards the interests of the market or customers. Therefore we so successful entrepreneurship, the necessary measures should be coupled with in order to create benefits for themselves and others with full sincerity to honesty, discipline, tenacity, creative and innovative in meeting the needs of many, so it will have an impact on the welfare of society a lot. Keywords: Tips, Success, Entrepreneur